BRAND GESTALT AS A KEY DETERMINANT OF TOURIST SATISFACTION AND LOYALTY: EMPIRICAL STUDY OF SUPER-PRIORITY DESTINATION LIKUPANG - Bervie Fransel Rondonuwu; Deske W. Mandagi (Jurnal Ekonomi, 2023)
Numerous researchers have conducted scholarly studies on the impact of tourist destinations on tourists' satisfaction and loyalty. However, research on the correlation between brand gestalt and tourist satisfaction and loyalty is still in its nascent stages. This study endeavors to investigate the effect of brand gestalt, which comprises diverse dimensions, including storyscape, sensescape, servicescape, and stakeholders, on the satisfaction and loyalty of local tourists in the Likupang beach tourism area of North Minahasa. A descriptive quantitative design was implemented, and primary data was gathered through a survey of 161 respondents who visited the Likupang beach tourism area of North Minahasa. Data analysis was performed using the Structural Equation Model (SEM), aided by the SmartPLS statistical application. The findings indicate that the sensescape and stakeholder dimensions are crucial predictors of tourist satisfaction. Additionally, the sensescape dimension exerts a significant and positive influence on tourist loyalty.